2021
DOI: 10.1088/1742-6596/1761/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative photoacoustic estimates of intervascular blood oxygenation differences using linear unmixing

Abstract: The linear unmixing technique is an appealing method for estimating blood oxygen saturation (sO2) from multiwavelength photoacoustic tomography images, as estimates can be acquired with a straightforward matrix inversion. However, the technique can only rarely provide accurate estimates in vivo, as it requires that the light fluence at the voxels of interest is constant with wavelength. One way to extend the set of cases where accurate information related to sO2 can be acquired with the technique is by taking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…To further demonstrate the clinical translation potential of the JAAZ particles, an in vivo pilot study was conducted on the commercially available small animal PAI system TriTom™ ( Fig. 6 A) [45] , [46] , [47] . We first acquired multiwavelength images of microcuvette tubes containing 0.4 mM of ICG dye or RGD-JAAZ particles to evaluate the PA spectra of both contrast agents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further demonstrate the clinical translation potential of the JAAZ particles, an in vivo pilot study was conducted on the commercially available small animal PAI system TriTom™ ( Fig. 6 A) [45] , [46] , [47] . We first acquired multiwavelength images of microcuvette tubes containing 0.4 mM of ICG dye or RGD-JAAZ particles to evaluate the PA spectra of both contrast agents.…”
Section: Resultsmentioning
confidence: 99%
“…6 E). Molecular maps were generated from a linear spectral unmixing of the multiwavelength PA images using previously reported spectra for hemoglobin and the measured spectra of the RGD-JAAZ particles at their injection concentration [47] , [48] .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the molecular maps of oxyhemoglobin, deoxyhemoglobin, and RGD-JAAZ particles show the biodistribution of the contrast agent is restricted to the vasculature and blood-rich tissues such as the liver and spleen (Figure 6E). Molecular maps were generated from a linear spectral unmixing of the multiwavelength PA images using previously reported spectra for hemoglobin and the measured spectra of the RGD-JAAZ particles at their injection concentration [45,46].…”
Section: Resultsmentioning
confidence: 99%
“…To further demonstrate the clinical translation potential of the JAAZ particles, an in vivo pilot study was conducted on the commercially available small animal PAI system TriTom™ (Figure 6A) [43][44][45]. We first acquired multiwavelength images of microcuvette tubes containing 0.4 mM of ICG dye or RGD-JAAZ particles to evaluate the PA spectra of both contrast agents.…”
Section: Pilot In-vivo Imaging Of Two Mice Using Rgd Functionalized J...mentioning
confidence: 99%
“…In our previous clinical study on the human calcaneus bone, wavelength-dependent light attenuation was partially addressed based on the bone model [ 25 ]. Previous studies from other groups have also indicated that spectral coloring can be eliminated using model-based or machine-learning-based methods [ [41] , [42] , [43] , [44] , [45] , [46] , [47] ]. Therefore, in future clinical studies, PA absorption curves affected by spectral coloring should be further studied and corrected.…”
Section: Discussionmentioning
confidence: 99%